Advanced training programmes in English as a medium of instruction to raise content teachers' motivation to deliver educational courses in English; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Francuzskaya E. O. Evgeniya Olegovna (2017, 2017)
Title screen